The Influence of Financial Attitude, Self Control, and Hedonism Style on Financial Management Behavior of Student Shopee Paylater Users in Jember District - Melia Feralda; Achmad Hasan Hafidzi; Ira Puspitadewi Samsuryaningrum (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to analyze the effect of financial attitude, self control and hedonism style on financial management behavior of female students of Shopee PayLater in Jember Regency. This research uses quantitative research with a descriptive approach. The population in this study were female students in Jember Regency who had used Shopee PayLater. The number of samples in this study were 385 respondents. In this research using Non Probability Sampling technique with purposive sampling technique and proportional sampling technique. The analysis technique used is multiple linear regression analysis. The results of this study indicate that the financial attitude variable has a significant positive effect on the financial management behavior of female Shopee PayLater users in Jember Regency, the self control variable has a significant positive effect on the financial management behavior of female Shopee PayLater users in Jember Regency, the hedonism style variable has a significant negative effect on management behavior the finance of student Shopee PayLater users in Jember Regency.